Penggunaan inovasi teknologi dalam perawatan di ruang intensif care unit: A literatur review - Mufimah, Mufimah; Monica, Rica; Firmansyah, Dedy; Kamaluddin, Ridlwan (Holistik Jurnal Kesehatan, 2025)
Background: Although the development of technology in health care in Indonesia has progressed, the application of technology in the ICU is still relatively limited. According to the Indonesian Ministry of Health (2024), several large hospitals in Jakarta and other big cities have implemented electronic-based patient data management systems and remote monitoring. However, it cannot be denied that there are still many hospitals in the regions that have not utilized technology optimally. Purpose: To analyze the use of technological innovation in intensive care unit care. Method:This research is a literature study with the PRISMA approach. Systematic review using PICO. The search databases used were PubMed/NCBI, Scopus and Sciencedirect with the keywords Innovation AND Technology AND Intensive Care Unit. Results: The types of technological innovations used in intensive care unit care are educational multimedia tools designed to improve ICU nurses' compliance with infection prevention and control practices, an intensive care telemedicine (tele-ICU) program called ERIC (Enhanced Recovery after Intensive Care), Ultrasonic technique Combination of Out-of-Plane Orientation and In-Plane Guidance for radial artery cannulation especially in shock patients in ICU, Virtual Reality (VR) to support the development of clinical decision-making skills, Remotely Tele-mentored Ultrasound (RTMUS) telemedicine to perform ultrasonography remotely. And each type of innovation technology used is significantly influential or effective according to the dependent variable measured. Conclusion: The use of technological innovation in intensive care unit care has been proven to provide benefits in all aspects, starting from infection prevention, quality indicators, and decision making.   Keywords: Innovation; Intensif Care Unit (ICU); Technology.   Pendahuluan: Perkembangan teknologi dalam perawatan kesehatan di Indonesia telah mengalami kemajuan, namun penerapan teknologi di ICU masih tergolong terbatas. Menurut Kemenkes RI (2024), beberapa rumah sakit besar di Jakarta dan kota-kota besar lainnya telah menerapkan sistem manajemen data pasien berbasis elektronik dan pemantauan jarak jauh. Namun tak dapat dipungkiri masih banyak rumah sakit di daerah yang belum memanfaatkan teknologi dengan optimal. Tujuan: Untuk menganalisis penggunaan  inovasi teknologi dalam perawatan di ruang intensif care unit. Metode: Penelitian literatur review dengan  pendekatan Preferred  Reporting  Items  for  Systematic  Reviews  and Meta-Analyses (PRISMA) dan menggunakan PICO. Database pencarian yang digunakan adalah pubmed/NCBI, Scopus,dan  Sciencedirect dengan  kata  kunci  "(Innovation) AND (Technology) AND (Intensif Care Unit)” Hasil: Jenis inovasi teknologi yang digunakan dalam perawatan di ruang intensif care unit yakni alat multimedia edukatif yang dirancang untuk meningkatkan kepatuhan perawat ICU terhadap praktik pencegahan dan pengendalian infeksi, program telemedis perawatan intensif (tele-ICU) bernama ERIC (Enhanced Recovery after Intensive Care), teknik Ultrasonik Kombinasi Out-of-Plane Orientation dan In-Plane Guidance untuk kanulasi arteri radial khususnya pada pasien syok di ICU, Virtual Reality (VR) untuk mendukung pengembangan kemampuan pengambilan keputusan klinis, Remotely Tele-mentored Ultrasound (RTMUS) telemedicine untuk melakukan ultrasonografi dari jarak jauh. Serta setiap jenis teknologi inovasi yang digunakan memberikan pengaruh atau efektif secara signifikan sesuai dengan variabel dependen yang diukur. Simpulan: Penggunaan inovasi teknologi dalam perawatan di ruang Intemsif care unit terbukti dapat memberikan manfaat pada segala aspek mula dari pencegahan infeksi, indicator mutu, dan pengambilan keputusan.   Kata Kunci: Intensif Care Unit (ICU); Inovasi ;Teknologi.